2023
DOI: 10.1097/hco.0000000000001031
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of atrial fibrillation

Abstract: Purpose of reviewAtrial fibrillation is the most common cardiac arrhythmia worldwide. There is considerable interest in better understanding the molecular genetics and biology of atrial fibrillation to inform the development of new therapies and improve clinical management. This review summarizes recent advances in our understanding of the genetic basis of atrial fibrillation and new efforts to utilize genetics to inform clinical management.Recent findingsGenome-wide association studies in diverse populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although the etiology of PoAF is complex, genetic factors may be associated with PoAF. 6) ApoE polymorphisms were previously reported to be associated with the familial form of AF. 9) However, to the best of our knowledge, only a few clinical studies verify the relationship between sporadic PoAF and ApoE polymorphisms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the etiology of PoAF is complex, genetic factors may be associated with PoAF. 6) ApoE polymorphisms were previously reported to be associated with the familial form of AF. 9) However, to the best of our knowledge, only a few clinical studies verify the relationship between sporadic PoAF and ApoE polymorphisms.…”
Section: Discussionmentioning
confidence: 98%
“…Although the etiology of PoAF is multifaceted, genetic factors may be associated with its occurrence. Genetic studies indicated several genetic loci in kindreds with a familial form of atrial fibrillation (AF), 6) but without clinical study to validate the effects in sporadic AF patients. Among these genetic loci, Apolipoprotein E (ApoE) is an important regulator of lipid metabolism and has three isoforms: 7) ApoE2, ApoE3, and ApoE4.…”
mentioning
confidence: 99%
“…Accumulating epidemiological evidence strongly indicates that the etiologies responsible for the development and maintenance of AF are extremely diverse and complex, and both environmental/non-genetical risk factors and heritable causative components may give rise to AF [ 2 , 51 , 52 , 53 ]. The already ascertained environmental/modifiable factors predisposing to AF encompass hypertrophic/dilated cardiomyopathy, coronary heart disease/acute myocardial infarction, valvular heart disease, essential hypertension, hyperthyroidism, diabetes mellitus, obstructive sleep apnea/hypopnea syndrome, an imbalanced cardiac autonomic nervous system, peri-atrial inflammation, β-thalassemia, metabolic disorder, obesity, smoking, alcohol consumption, and sedentary lifestyles [ 2 , 51 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, aggregating investigations have convincingly substantiated that genetic determinants exert critical roles in the initiation and perpetuation of AF, especially for idiopathic/familial AF, and, to date, a great number of rare AF-causing variations in >60 genes have been causally related to AF, amidst which the overwhelming majority encode ion channel subunits, myocardial structural proteins, signaling molecules, cardiac transcription factors, and connexins [ 52 , 53 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In addition, pan-genomic association research has revealed that common variants at ~140 genetic loci are implicated with enhanced vulnerability to AF, though merely a small fraction of these recognized variants have been experimentally validated to be pathogenic for AF thus far [ 52 ]. Notably, both rare mutations and common variations in the KCNH2 gene, which codes for the α subunit of the voltage-gated K + channel subfamily H member 2 and which has its expression transactivated by TBX20 [ 75 ], have been causally involved in AF [ 76 , 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, aggregating investigations have convincingly substantiated that genetic determinants exert critical roles in the initiation and perpetuation of AF, especially for idiopathic/familial AF, and, to date, a great number of rare AF-causing variations in >60 genes have been causally related to AF, amidst which the overwhelming majority encode ion channel subunits, myocardial structural proteins, signaling molecules, cardiac transcription factors, and connexins [52,53,[62][63][64][65][66][67][68][69][70][71][72][73][74]. In addition, pan-genomic association research has revealed that common variants at ~140 genetic loci are implicated with enhanced vulnerability to AF, though merely a small fraction of these recognized variants have been experimentally validated to be pathogenic for AF thus far [52]. Notably, both rare mutations and common variations in the KCNH2 gene, which codes for the α subunit of the voltagegated K + channel subfamily H member 2 and which has its expression transactivated by TBX20 [75], have been causally involved in AF [76][77][78].…”
Section: Introductionmentioning
confidence: 99%